Audit lags for local authorities in Malaysia / Asmah Abdul Aziz and Dyg Nazari Awg Drahman - Abdul Aziz, Asmah; Awg Drahman, Dyg Nazari (2004)
This research examines the audit certificates and financial statements of selected local authorities in Malaysia. The researchers investigate the duration of time taken by auditors to certify the annual accounts of selected local authorities, to determine whether the trend of audit lags have improved over time, and to present statistical evidence on audit lags in Malaysia. 59 audited financial statements of the selected local authorities were analysed for eleven years from year 1990 to 2000, i.e. 649 audited financial statements. Timely financial reports indicate that the management gives priority to the preparation of financial statements and disclosing the management of fund to the public. The study was conducted by document analysis and statistical investigation. It is revealed that the audit lags in Malaysia during the study period ranges between 2.92 months and 58.13 months. Only 3.7 percent of the audited accounts were certified within six months and 35.7 percent were certified after one year. 12.9 percent of the accounts were certified after two years. This means that many selected local authorities did not emphasise on the importance of timely financial reports. By the end of year 2000, the longest audit lag was 28.89 months. Thus although the situation has improved, the local authorities ought to publish the annual reports and accounts on time because this reflects the efficiency of the management and proves that the local authority is accountable to the public.